2017
DOI: 10.1002/anie.201707131
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Reforming of CO2 and CH4 into High‐Value Liquid Chemicals and Fuels at Room Temperature by Plasma‐Driven Catalysis

Abstract: The conversion of CO2 with CH4 into liquid fuels and chemicals in a single‐step catalytic process that bypasses the production of syngas remains a challenge. In this study, liquid fuels and chemicals (e.g., acetic acid, methanol, ethanol, and formaldehyde) were synthesized in a one‐step process from CO2 and CH4 at room temperature (30 °C) and atmospheric pressure for the first time by using a novel plasma reactor with a water electrode. The total selectivity to oxygenates was approximately 50–60 %, with acetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
243
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(248 citation statements)
references
References 50 publications
5
243
0
Order By: Relevance
“…This means that the coupling of the plasma with the catalyst did not generate a plasma‐catalytic synergy in NTP process. Nevertheless, Tu and Whitehead observed the plasma‐catalyst synergetic effect on DRM, which is dependent on packing methods . They found that, when the 10 wt% Ni/‐Al 2 O 3 catalyst in flake form calcined at 300°C was partially packed in the plasma, the synergy of plasma‐catalysis was clearly observed, leading to the doubled CH 4 conversion and H 2 yield (17.5%).…”
Section: Plasma‐assisted Conversion Of Ch4 and Co2mentioning
confidence: 99%
See 3 more Smart Citations
“…This means that the coupling of the plasma with the catalyst did not generate a plasma‐catalytic synergy in NTP process. Nevertheless, Tu and Whitehead observed the plasma‐catalyst synergetic effect on DRM, which is dependent on packing methods . They found that, when the 10 wt% Ni/‐Al 2 O 3 catalyst in flake form calcined at 300°C was partially packed in the plasma, the synergy of plasma‐catalysis was clearly observed, leading to the doubled CH 4 conversion and H 2 yield (17.5%).…”
Section: Plasma‐assisted Conversion Of Ch4 and Co2mentioning
confidence: 99%
“…The product distribution in solid catalyst‐plasma system can also be adjusted by introducing third gas (such as O 2 and Ar) into CH 4 /CO 2 . Very recently, Tu and coworkers reported the synthesis of liquid fuels and chemicals from CO 2 and CH 4 at room temperature and atmospheric pressure using a novel DBD plasma reactor with a water electrode . For the DBD plasma process without a catalyst, a total liquid selectivity of 59.1% was achieved with selectivities of 33.7, 11.9, 11.9, and 1.6% for acetic acid, ethanol, methanol, and acetone, respectively (in Figure A).…”
Section: Plasma‐assisted Conversion Of Ch4 and Co2mentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few decades, various atmospheric nonthermal plasma (NTP) technologies had been developed for direct methane conversion, including corona discharge, plasma jet, dielectric barrier discharge (DBD), pulsed discharge, spark discharge, gliding arc discharge, radio‐frequency discharge, and microwave discharge . The NTP technologies can generate high reactive species at relatively low temperature in favor of reducing the manufactory requirements and possibly enhancing the catalysis performance .…”
Section: Introductionmentioning
confidence: 99%